Le travail frontalier au Luxembourg et en Suisse. Similitudes, différences et défis communs - Pigeron-Piroth, Isabelle; Wille, Christian (Les travailleurs frontaliers au Luxembourg et en Suisse. Emploi, Quotidien et Perceptions, 2019)
Keywords: Grenzarbeitnehmer; Schweiz

Cross-Border Metropolitan Integration in Europe. The Case of Luxembourg, Basel, and Geneva. - Sohn, Christophe; Reitel, Bernard; Walther, Olivier (Environment and Planning C. Politics and Space, 2009)
Abstract: „In this paper we question the integration processes in three small cross-border metropolitan areas: Luxembourg, Basel, and Geneva. By referring to an original analysis framework, we evaluate the nature and intensity of the functional and institutional integration and highlight the elements that structure the cooperation between the actors. The analysis shows that there is not necessarily a reciprocal link between the size of the functional area and the extent of the cooperation. Whilst no metropolitan-sized organisation is on the agenda in Luxembourg, the example of Basel and Geneva shows that the presence of a national border offers an opportunity to invent original forms of governance, to increase the autonomy of the local authorities by different types of cooperation which transcend the institutional and territorial divides, and to promote the international character of the metropolitan centre. In a context of global competition, these features represent an undeniable benefit.“
Keywords: Basel; Genf; Schweiz; Soziale Integration; Stadt